Test of Preservative Content and Detection of Salmonella Sp. Bacterial Contamination in Salted Mackerel Meat (Rastrelliger Kanagurta) Sold at Pasar Galang, Deli Serdang Regency - Yulia Indriani; Marlinda Nilan Sari Rangkuti (Jurnal Pendidikan Sains dan Teknologi Terapan | E-ISSN : 3031-7983, 2024)
This research aims to determine the content of chemical preservatives such as formalin and borax, as well as detecting bacterial contamination of Salmonella sp. on salted mackerel fish sold at Galang Market. Formalin is detected using Potassium Permanganate (KMnO4) reagent, while borax is tested using H2SO4 reagent. To detect Salmonella sp. contamination, the test method is carried out using selective Salmonella Shigella Agar (SSA) media. The results of the research showed that the salted mackerel fish sold at Galang Market contained negative borax, this was indicated by the absence of changes in flame color that occurred on the porcelain cup during testing. The formalin content test of the three salted mackerel fish showed positive results for formalin content, this was indicated by a change in color to clear in the test tube. The results of the formalin level test in the first salted mackerel fish had a level of 1.61 mg/g, the second salted mackerel fish had a level of 1.55 mg/kg and the third salted fish had a formalin level of 1.65 mg/kg, already exceeding the acceptable tolerance threshold. accepted by the adult body. Salmonella sp. bacterial contamination test. The three salted mackerel fish tested produced negative results, indicating that the salted mackerel fish at Galang Market were free from Salmonella sp contamination.